The Influence of Understanding Social Media Ethics in Islam and Students' Perceptions of the Madrasa's Social Environment on Social Media Etiquette at Madrasah Tsanawiyah Masmur Pekanbaru - Hafif Kurniawan, Hafif Kurniawan; Zaitun; M.Fitriadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine the influence of students' understanding of social media ethics in Islam and their perceptions of the social environment of the madrasa on social media etiquette at Madrasah Tsanawiyah Masmur Pekanbaru, both partially and simultaneously. This research uses a quantitative approach with a field research method. The population in this study consists of 105 students, with a sample of 83 students selected using the Slovin formula and stratified random sampling technique. Data collection was carried out through tests, questionnaires, and documentation. The data analysis technique used inferential statistics with a multiple linear regression model. The results of the study indicate that in the first hypothesis, there is a significant influence of the understanding of social media ethics in Islam (X1) on students' social media etiquette (Y), with a significance value of 0.020 (Sig. 0.020 < 0.05) and a t-count value of 2.378 (t-count 2.378 > t-table 1.990). The second hypothesis shows that there is also a significant influence of students' perceptions of the madrasa's social environment (X2) on students' social media etiquette (Y), with a significance value of 0.000 (Sig. 0.000 < 0.05) and a t-count value of 7.061 (t-count 7.061 > t-table 1.990). In the third hypothesis, there is an influence of both independent variables (X1 and X2) simultaneously on students' social media etiquette (Y), with a significance value of 0.000 (Sig. 0.000 < 0.05) and an F-count value of 34.756 (F-count 34.756 > F-table 3.109). In addition, the R Square value of 0.465 indicates that 46.5% of the variation in students' social media etiquette can be explained by both independent variables simultaneously, while the remaining 53.5% is influenced by other factors not included in this regression model. The results of this study emphasize the importance of understanding social media ethics in Islam and students' perceptions of the madrasa's social environment in shaping students' social media etiquette.